Penggunaan Teknologi dalam Strategi Pembelajaran Pendidikan Islam - Zaini Hartika; Siti Badriyah; Gusmaneli Gusmaneli (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the application of technology in Islamic Religious Education (IRE) learning, focusing on the challenges and obstacles encountered, as well as the changes in the role of teachers in technology-based learning strategies. The approach used is a descriptive qualitative method with library research as the primary technique. Through the analysis of various relevant literatures, this study identifies the potential of technology in enhancing the effectiveness of IRE learning, as well as obstacles such as limited access to technology, skill gaps, and dependency on technology. Additionally, this study explores the transformation of the teacher's role from being an instructor to a facilitator, who focuses more on managing technology and creating a safe and inclusive learning environment. The findings of this study indicate that despite the challenges, technology holds significant potential to improve the quality of religious education, provided that efforts are made to overcome the existing barriers.